I spy mystery : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Scholastic, 1993)
Rhyming verses ask readers to find hidden objects in the photographs.
"Cartwheel books."
Publisher's Weekly
School Library Journal
Wilson's Children
3.0
K-3.
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles; Picture puzzles